Ab initio and DFT Studies on Tautomerization of Nitrosamine in Reaction of the Nitrosamine Isomers-H2O2 - Bavafa, Sadeghali (Asian Journal of Chemistry, 2010)
Ab initio molecular orbital and DFT calculations have been carried out for tautomerization, 2 imino tautomers and 1 zwitter ionic to amino (most stable species of the nitrosamine isomers) in reaction of HNNOH-H2O2 in order to elucidate the structures and energetics. The structures and transition states were optimized using B3LYP and MP2 methods with 6-311++G(2d,2p), AUGcc- pVDZ basis sets. The transition states of the three transformation reactions found in the study possess 3 proton-transfer processes. Energetics and thermodynamic properties of all tautomerization of nitrosamine in reaction of the nitrosamine isomers -H2O2 have been obtained.